E. Help Desk: A natural language processing for answering query / Norwin Shariman Mohd. Nor - Norwin Shariman, Mohd. Nor (2001)
This report is about a search engine, E. Help Desk that is to be deployed in a location where usually the users have a brief contact with the search engine. Thus it is designed to be very easy to use as it is designed to be intuitive, so as the learning curve for the search engine is very shallow. The system is divided into two modules, the user interface and the administrator module. The user interface provide· a basic search engine capability to the user to enable them to search for relevant article. In regard to place like a shopping complex, for instance the user can search for shops and public amnesties. The administrator module provides the capability for the people involved in the maintenance to update the information. This will be very useful in some application where the information changes often. The designing of the system uses the software engineering methodology to enable the designing of a system that are relatively trouble free. Thus, the authour tries to make sure that every aspect in the development be planned.